A Systematic Mapping Study of Innovative Cloud Applications. Issue 1 (April 2020) - Odun-Ayo, I; Williams, T; Iheanetu, Olamma; Odusami, Modupe; Bogle, Sherenne
Abstract: Cloud computing is a business paradigm wherein computers and computing related services are provided by Cloud Service Providers to consumers either as software, development platform, or infrastructure. Innovative applications are growing in a productive manner on the cloud landscape. Innovative applications are being developed for use in the area of e-learning, automotive processes, cloud containers and machine learning. The objective of this paper is to conduct a systematic mapping study of innovative cloud applications and experiences. The systematic map provided a structured overview of research work carried out and the frequency of publications, presenting them pictorially in form of a map. The obtained results showed that 7.34% of the publications were on development of innovative cloud applications in terms of model. Architecture and modelling, and simulation in relation to model were both at 13.76%, 11.93% of the papers respectively, while 8.26% of the articles were on deployment in terms of process. Architecture had most publication in the area of solution research, with 15.2%. For articles published on deployment and development, most were on solution research with 8.80% and 14.40% respectively. The outcome of this study will be beneficial to practitioners in the industry and academic researchers alike.